Measures of three-dimensional anisotropy and intermittency in strong Alfvénic turbulence - Mallet,A; Schekochihin,AA; Chandran,BDG; Chen,CHK; Horbury,TS; Wicks,RT; Greenan,CC (Monthly Notices of the Royal Astronomical Society, 2016)
We measure the local anisotropy of numerically simulated strong Alfvénic turbulence with respect to two local, physically relevant directions: along the local mean magnetic field and along the local direction of one of the fluctuating Elsasser fields. We find significant scaling anisotropy with respect to both these directions: the fluctuations are ‘ribbon-like’ – statistically, they are elongated along both the mean magnetic field and the fluctuating field. The latter form of anisotropy is due to scale-dependent alignment of the fluctuating fields. The intermittent scalings of the nth-order conditional structure functions in the direction perpendicular to both the local mean field and the fluctuations agree well with the theory of Chandran, Schekochihin & Mallet, while the parallel scalings are consistent with those implied by the critical-balance conjecture. We quantify the relationship between the perpendicular scalings and those in the fluctuation and parallel directions, and find that the scaling exponent of the perpendicular anisotropy (i.e. of the aspect ratio of the Alfvénic structures in the plane perpendicular to the mean magnetic field) depends on the amplitude of the fluctuations. This is shown to be equivalent to the anticorrelation of fluctuation amplitude and alignment at each scale. The dependence of the anisotropy on amplitude is shown to be more significant for the anisotropy between the perpendicular and fluctuation-direction scales than it is between the perpendicular and parallel scales.